Down regulation of cyclooxygenase-2 is involved in delayed neuroprotec- tion by ischemic preconditioning in rats - XIAO Liang; ZHAO Fei-li; ZHU Xing-zu (Acta Pharmacologica Sinica, 2016)
Aim: To examine whether the prostaglandins (PGs) pathway is involved in triggering delayed neuroprotection by ischemic preconditioning (IPC) and evaluate the effects of IPC on cyclooxygenase-2 (COX-2) expression following focal cerebral ischemia and reperfusion in rats. Methods: IPC was induced by 10 min of saline infusion into the left internal carotid artery with the right common carotid artery clamped at the same time. Middle cerebral artery occlusion (MCAO) and reperfusion model was produced using intraluminal filament method. Results: IPC 48 h prior to MCAO significantly reduced infarct area as compared with MCAO alone. A nonselective inhibitor of COX indomethacin (3 mg/kg ip) applied 1 h prior to or 1 h after IPC failed to affect its protective effects. IPC had no direct effect on the cortex COX-2 mRNA and protein expression 72 h later, but decreased the expression of COX-2 mRNA and protein following ischemia and reperfusion insult. Conclusion: PGs pathways was not involved in triggering delayed neuroprotection by IPC, and IPC induced down-regulation of COX-2 following focal cerebral ischemia and reperfusion in rats in vivo.